2008
DOI: 10.1002/ceat.200800116
|View full text |Cite
|
Sign up to set email alerts
|

Dividing Wall Distillation Columns: Optimization and Control Properties

Abstract: The optimal design of dividing wall columns is a non-linear and multivariable problem, and the objective function used as optimization criterion is generally non-convex with several local optimums. Considering this fact, in this paper, we studied the design of dividing wall columns using as a design tool, a multi-objective genetic algorithm with restrictions, written in Matlab TM and using the process simulator Aspen Plus TM for the evaluation of the objective function. Numerical performance of this method has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 29 publications
3
48
0
Order By: Relevance
“…In this case we cover a sufficiently complete range of frequencies. Similar studies have been reported by Jantes-Jaramillo et al (2008) and Gómez-Castro et al (2008), among others, for control analysis in studies of thermally coupled distillation systems.…”
Section: Singular Value Decomposition (Svd)supporting
confidence: 86%
“…In this case we cover a sufficiently complete range of frequencies. Similar studies have been reported by Jantes-Jaramillo et al (2008) and Gómez-Castro et al (2008), among others, for control analysis in studies of thermally coupled distillation systems.…”
Section: Singular Value Decomposition (Svd)supporting
confidence: 86%
“…In this case a sufficiently complete range of frequencies was covered. Similar studies have been reported by Jantes-Jaramillo et al [23], Gómez-Castro et al [18,24], and Ibarra-Sánchez and Segovia-Hernández [25] among others, for the control analysis of complex distillation systems. Other techniques available for the dynamic analysis of distillation systems are the relative gain array (RGA) analysis and the Niederlinski Index (NI) analysis, which allows to determinate the best pairing alternatives between control loops [26].…”
Section: Singular Value Decomposition Technique (Svd)supporting
confidence: 85%
“…Even nowadays some plants still work with column sequences that are suboptimal compared with some thermally couple arrangements. However, extended studies about operation and controllability showed that TCD with or without DWCs can be satisfactorily operated [1,[51][52][53][54][55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%